DAMPAK PENGUNGKAPAN MODAL INTELEKTUAL PADA BIAYA EKUITAS - Rohma, Elis Nur; Subroto, Bambang (Jurnal Ilmiah Mahasiswa FEB, 2016)
Examining the impact of intellectual capital disclosure on cost of equity capital is the aim of this study. Intellectual capital’s components tested are the internal structure, competence of employees, and external structure disclosure. This study use purposive sampling to generate 84 companies listed in Indonesia Stock Exchange (BEI) during 2012. The results show that the intellectual capital disclosure, each of internal structure, employee competence, and external structure disclosure has negative relationship on the cost of equity capital. The impact of the cost of equity capital is affected most by the internal structure than the employee competence and external structure disclosure. Keywords: Cost of Equity Capital, Employee Competence, External Structure, Intellectual Capital Disclosures, Internal Structure.